2010
DOI: 10.1039/b909662k
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated diffusion in reversibly associating polymers

Abstract: Mass transport of a small molecule dye through dynamic polymer networks containing reversibly associating side-groups was directly compared to steady-shear viscosity measurements suggesting that viscous relaxation is limited more by the frequency of dissociation events while mass transport is determined primarily by the degree of association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Similarly, by studying both macroscopic shear behavior and the microscopic diffusion of a low molecular weight dye in polymer melts that consist of chains with self-complementary, reversibly associating UPy side groups, Anthamatten et al 212 showed that the macroscopic sample viscosity is determined by the UPy dissociation rate, whereas the transport of the dye through the network is dominated by the equilibrium constant of the UPy association and dissociation. The authors explain this result by considering that the fragments of a broken UPy associate are immediately torn away from each other under shear, such that recombination is likely to occur with a different broken associate, as shown in Fig.…”
Section: Dynamicsmentioning
confidence: 99%
“…Similarly, by studying both macroscopic shear behavior and the microscopic diffusion of a low molecular weight dye in polymer melts that consist of chains with self-complementary, reversibly associating UPy side groups, Anthamatten et al 212 showed that the macroscopic sample viscosity is determined by the UPy dissociation rate, whereas the transport of the dye through the network is dominated by the equilibrium constant of the UPy association and dissociation. The authors explain this result by considering that the fragments of a broken UPy associate are immediately torn away from each other under shear, such that recombination is likely to occur with a different broken associate, as shown in Fig.…”
Section: Dynamicsmentioning
confidence: 99%
“…For example, our group and others have previously shown that viscous relaxation in hydrophobic polymers bearing UPy side-groups is limited by the H-bonding dissociation rate. 18,28 For samples bearing UPy side-groups, swelling is signicantly slower and the thermal activation barrier is higher. Higher temperatures correspond to faster side-group rearrangement thereby hastening viscous relaxation, and, consequently, swelling.…”
Section: Water Swelling Behaviormentioning
confidence: 99%
“…We have recently investigated the viscoelastic properties of low glass transition temperature polymers and elastomers that contain UPy-terminated side-groups. [17][18][19] The combination of covalent and non-covalent crosslinks gives rise to a broad dynamic viscoelastic transition, forming the basis for novel shape memory elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…The original “spot” FRAP technique has undergone a variety of modifications to accommodate different photobleaching methods, including patterned (Abney et al 1992), continuous (Wedekind et al 1996), line (Braeckmans et al 2007), and disc-shaped (Mazza et al 2008) photobleaching. Modifications to the recovery analysis have also expanded FRAP as a tool to analyze binding kinetics (Kaufmann and Jain 1991; Berk et al 1997; Schulmeister et al 2008), to quantify the connectivity of compartments (Majewska et al 2000; Cardarelli et al 2007), and to investigate polymer structure-property relationships (Li et al Submitted). …”
Section: Introductionmentioning
confidence: 99%